Pulse therapy with cyclophosphamide and methylprednisolone in patients with moderate to severe paraquat poisoning: a preliminary report. Issue 7 (July 1996) - Lin, J. L.; Wei, M. C.; Liu, Y. C.
Abstract : BACKGROUND: Severe paraquat poisoning causes considerable morbidity and mortality. High doses of cyclophosphamide and dexamethasone have been used to treat patients with paraquat poisoning, but with mixed results. The use of pulse methylprednisolone and cyclophosphamide was investigated in the treatment of moderately severe paraquat poisoning. METHODS: During a six-year period 87 patients with paraquat poisoning were admitted to hospital, of whom 33 had moderate to severe intoxication. Seventeen patients received conventional treatment and served as historical controls, and 16 received intravenous infusions of cyclophosphamide 1 g daily for two days and methylprednisolone 1 g daily for three days. RESULTS: There were no differences between the groups in age, sex, severity of paraquat poisoning (as assessed by urine dithionite tests), or in the time elapsed from ingestion to presentation at hospital or to the beginning of haemoperfusion. No differences were seen in biochemical measurements on the third day after paraquat poisoning. The mortality in the pulse therapy group was lower than that in the control group (4/16 (25%) versus 12/17 (70.6%), p = 0.01). All fatalities were from progressive respiratory failure. CONCLUSIONS: Pulse therapy with cyclophosphamide and methylprednisolone may be effective in preventing respiratory failure and reducing mortality in patients with moderate to severe paraquat poisoning. Further controlled studies are needed to confirm this and to establish the mechanisms.